2006
DOI: 10.1128/jvi.80.8.3743-3751.2006
|View full text |Cite
|
Sign up to set email alerts
|

Functional Mapping of the Nucleoprotein of Ebola Virus

Abstract: ) previously demonstrated that NP, together with the minor matrix protein VP24 and polymerase cofactor VP35, is necessary and sufficient for the formation of nucleocapsid-like structures that are morphologically indistinguishable from those seen in Ebola virus-infected cells. They further showed that NP is O glycosylated and sialylated and that these modifications are important for interaction between NP and VP35. However, little is known about the structure-function relationship of Ebola virus NP. Here, we ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
177
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 155 publications
(186 citation statements)
references
References 38 publications
8
177
0
1
Order By: Relevance
“…According to this model, NP forms helical tubes which differ from nucleocapsid-like structures. VP35 and VP24 interact with the pre-formed NP-derived helices, resulting in the formation of nucleocapsid-like structures [36]. Both transport of the nucleocapsids to the plasma membrane and incorporation into virions are mediated by the interaction of NP with VP40 [23,37].…”
Section: Nucleocapsid Assemblymentioning
confidence: 99%
“…According to this model, NP forms helical tubes which differ from nucleocapsid-like structures. VP35 and VP24 interact with the pre-formed NP-derived helices, resulting in the formation of nucleocapsid-like structures [36]. Both transport of the nucleocapsids to the plasma membrane and incorporation into virions are mediated by the interaction of NP with VP40 [23,37].…”
Section: Nucleocapsid Assemblymentioning
confidence: 99%
“…The NP of ebolavirus is necessary and sufficient for the formation of nucleocapsid-like structures in a mammalian expression system. It is also responsible for the NP-NP interaction and replication of the viral genome (Watanabe et al, 2006). Xu (2014) showed that VP24 binds to the karyopherin alpha nuclear transporters and blocks the nuclear accumulation of STAT1, a very important component of the immune system (Xu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…NP encapsidates the genome and protects it from nucleases. 17,18 VP30 is a transcription anti-terminator 19,20 and regulates the switch between transcription and replication. 21,22 VP35 acts as a cofactor of the polymerase, 23,24 and VP40 may also play a role in genome replication and transcription.…”
Section: Introductionmentioning
confidence: 99%